The Possible Role of Rosuvastatin Therapy in HFpEF Patients—A Preliminary Report - Tomasz Urbanowicz; Ievgen Spasenenko; Marta Banaszkiewicz; Anna Olasińska-Wiśniewska; Aleksandra Krasińska-Płachta; Andrzej Tykarski; Krzysztof J. Filipiak; Zbigniew Krasiński; Beata Krasińska (Diagnostics)
Background: An increasing number of heart failure with preserved ejection fraction (HFpEF) syndromes has been reported in tandem with increasing age and burdens of obesity and cardiometabolic disorders. Identifying possible risk and modulatory HFpEF factors has significant epidemiological and clinical value. This study aimed to assess the prevalence of echocardiographic diagnostic criteria of left ventricular dysfunction in patients with chronic coronary syndrome depending on rosuvastatin therapy. Method: There were 81 (33 (41%) male) consecutive patients with a median age of 70 (62–75) years, presenting with stable heart failure symptoms according to the New York Heart Association (NYHA) classification I to III. They presented with chronic coronary syndrome and were hospitalized between March and August 2024. Patients were divided according to the type of long-term lipid-lowering therapy into patients with rosuvastatin and with other statin therapy. The echocardiographic analysis based on diastolic dysfunction evaluation was performed on admission and compared with demographical, clinical, and laboratory results. Results: In the multivariable model for diastolic dysfunction prediction in the analyzed group based on three echocardiographic parameters, septal E’ below 7 cm/s, lateral E’ below 10 cm/s, and LAVI above 34 mL/m2, the following factors were found to be significant: sex (male) (OR: 0.19, 95% CI: 0.04–0.83, p = 0.027), obesity (defined as BMI > 30) (OR: 12.78, 95% CI: 2.19–74.50, p = 0.005), and rosuvastatin therapy (OR: 0.09, 95% CI: 0.02–0.51, p = 0.007). Conclusions: Rosuvastatin therapy can be regarded as a possible protective therapy against left ventricular diastolic dysfunction in chronic coronary syndrome.